Distance and E-Supervising: Experiences and Results - Hacene, HAMADA (Journal of Human Sciences, 2011)
This paper presents samples of electronic and distance supervision of Doctorate theses and Magister dissertations, step by step, from research proposal to viva presentation. The method proves to save time and energy for both supervisors and candidates and keeps permanent contact between the candidates and continuous follow-up of research progression by the supervisor and the research institution